2020
DOI: 10.18690/978-961-286-402-6
|View full text |Cite
|
Sign up to set email alerts
|

Likovna apreciacija v vzgoji in izobraževanju: Primeri kvalitativnih raziskav

Abstract: Znanstvena monografija obsega šest glavnih poglavij. V Uvodu sta predstavljeni ustvarjalnost in apreciacija kot dva temeljna vidika pouka likovne umetnosti. V nadaljevanju, Terminološka opredelitev likovne apreciacije, je razvoj termina likovna apreciacija opredeljen na osnovi poznanih strokovnih razprav. V poglavju Osnovne značilnosti likovne apreciacije so opisani dejavniki likovne apreciacije. V poglavju Struktura likovne apreciacije sta predstavljena likovno znanje in čas kot pomembna dejavnika pri razvoju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Six categories are used to measure creativity today: sensitivity to problems (perception of artistic values), elaboration (organisation and use of artistic elements), flexibility (adaptation by means of artistic expression), fluency (a wealth of artistic ideas), originality (unusual and individual realisation) and redefinition (which also connects the redefinition of previous art experiences into new art structures) (Tomljenović, 2015). Several authors (Duh, 2004(Duh, , 2018Duh & Büdefeld, 2018;Herzog, 2008Herzog, , 2009 categorise the factors of artistic creativity into two groups. The first factors promote quantity and enable artistic creativity (redefinition, fluency and elaboration), while the other factors activate quality and promote artistic creativity (originality, flexibility and sensitivity to artistic language).…”
Section: Artistic Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six categories are used to measure creativity today: sensitivity to problems (perception of artistic values), elaboration (organisation and use of artistic elements), flexibility (adaptation by means of artistic expression), fluency (a wealth of artistic ideas), originality (unusual and individual realisation) and redefinition (which also connects the redefinition of previous art experiences into new art structures) (Tomljenović, 2015). Several authors (Duh, 2004(Duh, , 2018Duh & Büdefeld, 2018;Herzog, 2008Herzog, , 2009 categorise the factors of artistic creativity into two groups. The first factors promote quantity and enable artistic creativity (redefinition, fluency and elaboration), while the other factors activate quality and promote artistic creativity (originality, flexibility and sensitivity to artistic language).…”
Section: Artistic Expressionmentioning
confidence: 99%
“…Such openness to adaptation enables the ability to engage flexibly with new things (DeYoung, 2006). Sensitivity to artistic language is a factor where one immediately notices what is important in the artistic interpretation of motifs (Duh, 2004). Karlavaris (1974) states that sensitivity towards artistic language is the ability of the individual to recognise and experience an artistic motif and to choose the appropriate material for the interpretation and creation of a new artistic whole.…”
Section: Artistic Expressionmentioning
confidence: 99%
“…Also derived from these phases are the didactic aspects of planning educational content in the school subject of arts. When, however, the creative development of learners is monitored in research (Karlavaris & Kraguljac, 1981;Duh, 2004;Herzog, 2009), six agents are observed that either allow or promote creativity (see Table 1 below). The agents that allow artistic creativity are redefinition, fluency and elaboration.…”
Section: Introductionmentioning
confidence: 99%
“…The agents that promote artistic creativity are originality, flexibility and sensitivity to artistic problems. Likewise, these agents also contain the weaker factor that allows artistic creativity (Duh, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fine arts class is an educational process where students are also co-creators of the learning process. One of the fundamental aspects of fine arts as a school subject is the development of creativity, which is the actual process of artistic creativity through which the students obtain their skills and techniques (Duh & Herzog, 2020).…”
Section: Introductionmentioning
confidence: 99%